Feasibility study of ED‐XRF analysis of atmospheric particulate matter samples collected with high time resolution1. (28th April 2015) - Giannoni, M.; Calzolai, G.; Chiari, M.; Lucarelli, F.; Mazzinghi, A.; Nava, S.; Ruberto, C.
<x xml:space="preserve">Abstract</x> This study aims at verifying the feasibility of the analysis of particulate matter samples collected with hourly time resolution by a Streaker sampler device, using cheaper and more affordable instrumentations like energy dispersive X‐ray fluorescence (ED‐XRF) spectrometers. The 'hourly' samples are not analysable with the available commercial laboratory ED‐XRF spectrometers, because the aerosol deposit forms a continuous streak that has to be analysed 'point‐by‐point' with a collimated beam of a few mm size. For this specific application, a custom‐made compact XRF spectrometer, designed at the INFN LABEC laboratory in Florence and typically used for in‐situ analysis of cultural heritage, has been used. This ED‐XRF system is based on the combined use of two X‐ray tubes with different anodes (Mo and Ti), a 30‐mm2 silicon drift detector and a helium flow to reduce the attenuation of low energy X‐rays. A set of elemental thin standards containing elements from Na to Pb has been analysed in order to determine the best experimental conditions, the sensitivity and the detection limits of this system. The results of quantitative analysis on certified aerosol samples, on particulate matter samples collected for 24 h by a low volume sampler and on Streaker samples ('fine' fraction, PM2.5) are in good agreement with those obtained by PIXE and polarized optics ED‐XRF measurements. This study demonstrates that a specialized custom‐made ED‐XRF system may represent a promising solution for elemental analysis of Streaker samples, even for low‐Z elements, although PIXE technique still remains unrivalled as regards sensitivity and measurement throughput. Copyright © 2015 John Wiley & Sons, Ltd.